We Will Create a Demonstration Zone for Green Finance Reform and Innovation in Southern Sichuan and Western Chongqing—Accelerate the Pace of Financial Integration in the Chengdu-Chongqing Twin Cities Economic Circle - Lin, Sun; Wantong, Liao (Journal of Global Economy, Business and Finance, 2025)
The southern Sichuan and western Chongqing region is the area with the most prominent regional advantages, strongest carrying capacity, and best industrial foundation in the Chengdu-Chongqing region outside of the dual-core areas of Chongqing and Chengdu. Since the issuance of the “General Plan for Promoting the Integrated Development of Southern Sichuan and Western Chongqing” by both Chongqing and Sichuan, this region has gradually begun to explore and integrate related industries, achieving positive results. However, due to national financial management policies, the integration of finance in the southern Sichuan and western Chongqing region has been relatively slow. How to accelerate the integrated development of finance in the southern Sichuan and western Chongqing region has become an important issue at present. Establishing a national green finance innovation and reform demonstration zone provides a new solution. This paper starts from the current status of green finance nationwide and in the southern Sichuan and western Chongqing region, analyzes the policy, standard, and supply issues existing in the creation of a green finance innovation and reform demonstration zone in the southern Sichuan and western Chongqing region, and proposes corresponding countermeasures and suggestions, providing a reference for accelerating the financial integration development of the Chengdu-Chongqing dual-city economic circle.